Behavioural Descriptions of Indian Pangolins (Manis crassicaudata) in Captivity - Mohapatra, Rajesh Kumar; Panda, Sudarsan (International Journal of Zoology, 2014)
Conservation breeding programmes as an essential tool for conservation of endangered species require a sound knowledge on behaviour of the species. At present time, knowledge of behaviour and biology of Indian pangolins is inadequate and inconsistent. During the present study, an ethogram was developed based on the behavioural observations of seven Indian pangolins (Manis crassicaudata) at Pangolin Conservation Breeding Centre, Nandankanan Zoological Park, Odisha, India, between February 2012 and January 2013. A total of 27 behaviours of seven distinct behavioural categories (stationary body positions, locomotory patterns, maintenance behaviours, explorative behaviours, defensive behaviours, reproductive/social behaviours, and others) were described and illustrated. The results offer a consistent frame of reference for further studies on behavioural patterns of Indian pangolins. Besides, these preliminary observations could be useful in management and breeding of the species in captivity.